Hospitalisation for monkeypox in Milan, Italy. Issue 49 (September 2022) - Moschese, Davide; Giacomelli, Andrea; Beltrami, Martina; Pozza, Giacomo; Mileto, Davide; Reato, Serena; Zacheo, Martina; Corbellino, Mario; Rizzardini, Giuliano; Antinori, Spinello
Abstract: During the current multi-country outbreak of human monkeypox the hospitalisation rate observed in Milan, Italy was 8.8%. Bacterial superinfection and severe perianal pain were the main cause of hospitalisation requiring antibiotic treatment and analgesic therapy. One patient was treated with Cidofovir. All hospitalised patients were discharged and the outcome was favourable with full recovery.